DETERMINANTS OF FINANCIAL INCLUSION IN SOUTHERN AFRICA - MHLANGA, David; DENHERE, Varaidzo (Studia Universitatis Babeș-Bolyai Oeconomica, 2022)
The study sought to establish the drivers of financial inclusion in Southern Africa with a specific focus on South Africa. Financial inclusion has been a topic of global interest due to the negative impact of financial exclusion in addressing socio-economic issues like poverty. Using the logit model, the study discovered that financial inclusion is driven by age, education level, the total salary proxy of income, race, gender, and marital status. The variable gender was the only factor with a negative influence on financial inclusion all other significant variables had a positive influence on financial inclusion. As a result, governments in Africa should encourage the use of financial services and products among women, Black Africans, Coloureds and the youths. Products and services tailor-made to satisfy the needs of these groups should be designed to improve financial inclusion among them. This initiative will go a long way in addressing poverty, inequality, and unemployment in the country. JEL classification: G1, O12, G23, G38